Influence of Slip Velocity and Aligned Magnetohydrodynamics on Convective Boundary Layer Flow of Jeffrey Fluid with Convective Boundary Condition Across Stretching Sheet - Al-Sharifi, H. A. M.; L. A., Aziz; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; S., Shafie (Universiti Malaysia Pahang, 2016)
The solutions on the flow and heat transfer of a Jeffrey fluid on a stretching sheet with effect of aligned Magnetohydrodynamics (MHD) is presented in this paper. The governing non-linear equations are first transformed into ordinary differential equations using appropriate transformation before solving using BVP4C. In order to verified the correctness of the present computation, the comparison on the limiting case with the previous publication has been made and the results shows an excellent agreement.